Recruitment to clinical trials in labour: holds experience. (18th April 2012) - Armstrong, N; McNicol, S; Willars, J; Markham, C; Kenyon, S
Abstract : Background: Recruitment when eligibility can only be confirmed during labour is challenging, particularly for indications that occur infrequently. Currently the Royal College of Obstetricians and Gynaecologists advises that in such situations all potentially eligible women should receive antenatal information, and consent be taken when the woman becomes eligible for inclusion.1 Methods: The HOLDS pilot ran in three centres between November 2010 and May 2011 and recruited 94 women to a pilot trial of standard versus high dose oxytocin for nulliparous women with confirmed delay in labour. The RCOG model was adopted and this paper reports qualitative data from semi-structured interviews with a diverse sample of 18 women approximately six weeks after birth, who were recruited to the pilot in labour. Data was analysed using the constant comparative method. Results: Only four of the eighteen women remembered receiving the information antenatally, and those that did remember said it did not seem relevant to them. Fourteen of the eighteen women interviewed had at least a basic understanding of what was involved and felt able to give informed consent at the time. Two women could not recall details but trusted clinical staff. All were happy they had participated. Verbal information from clinicians to support that provided was important to participants' decision, as was support from partner present. Conclusions: The current RCOG advice regarding information to all potentially eligible women in the antenatal period may not be seen as relevant by women, nor influence their ability to give informed consent in situations that occur infrequently.